Reflecting on Ethics in Practice Neuromarketing: Neuroethics - Santos, Marcos Ferreira (2014)
This article aims to answer to the following research problem: what are the relevant ethical questions related to neuromarketing practice? The objective is to explain the evolution of the field of neuromarketing from neurosciences and neuroeconomics; explain the main research techniques used on neuromarketing; to present the neuroethics field and apply the concept to the relevant ethical questions of the neuromarketing practice. Neuromarketing developed from neuroeconomics. By using the same techniques of image mapping, neuromarketing aims to investigate consumer behavior and utilize this information on marketing actions. The field of neuroethics can be understood as a reflection of the neuroscientific practices and ethical concepts. Questions of interest to neuroethics involve the practical applications of neurotechnology for people and the society in general. Marketing is a business activity with social implications and, therefore, cant be done in the absence of values. This article contributes for the academic knowledge of neuromarketing beginning from a revision of international journals and the presentation of a new field of neuromarketing not discussed before by the academy in Brazil: neuroethics. The reflection about the ethics in the neuromarketing practice, neuroethics, its important to guide future and present researches in this field.